Definition of Collections, Standards and Procedures for Retrospective Digitisation - Bakker, Trix (LIBER Quarterly: The Journal of the Association of European Research Libraries, 1999)
This paper is the result of (literature) research and expertise acquired by digitisation projects in the Koninklijke Bibliotheek (KB). The project described is part of the DELTA project, a joint project of Dutch university libraries together with Pica, which focuses on integration of existing and new local and central services into one integrated end-user service. Aim of this (sub)project is to establish a common working procedure within each library and between libraries to improve interoperability, exchange of expertise and to provide the basis for combining dispersed collections in a virtual digital library. During the project selection criteria were developed, five scholarly core journals of international reputation and use were selected, an organisation model was developed, costs were estimated, and decided was to work according to a simple hybrid model e.g. microfilming and digitisation of articles: the backfiles will be scanned in 400-600 dpi and made available in PDF, and the tables of contents in HTML. The articles will be catalogued in the central Pica database and are accessible via the Online Contents (OLC) database and PiCarta, an integrated, multimaterial database offering access to online resources and electronic documents. Copyright will be cleared individually with the Dutch publishers. Part of the project is to develop draft license agreements with different kind of publishers. Archiving will be integrated into the DNEP (Deposit of Dutch Electronic Publications) service of the Koninklijke Bibliotheek.